2020
DOI: 10.1007/s00228-020-03052-2
|View full text |Cite
|
Sign up to set email alerts
|

Potentially inappropriate prescribing in older hospitalized Dutch patients according to the STOPP/START criteria v2: a longitudinal study

Abstract: Purpose To investigate prevalence, independent associations, and variation over time of potentially inappropriate prescriptions in a population of older hospitalized patients. Methods A longitudinal study using a large dataset of hospital admissions of older patients (≥ 70 years) based on an electronic health records cohort including data from 2015 to 2019. Potentially inappropriate medication (PIM) and potential prescribing omission (PPO) prevalence during hospital stay were identified based on the Dutch STO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
1
10
1
1
Order By: Relevance
“…Consistent with other studies, the multivariate logistic regression identified several age-specific factors associated with multimorbidity, polypharmacy, and PIM use [ 38 , 39 , 40 , 41 , 42 , 43 ]. As a rule of thumb, many body functions decline in old age, which is a frequent cause of multimorbidity [ 1 , 10 , 14 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with other studies, the multivariate logistic regression identified several age-specific factors associated with multimorbidity, polypharmacy, and PIM use [ 38 , 39 , 40 , 41 , 42 , 43 ]. As a rule of thumb, many body functions decline in old age, which is a frequent cause of multimorbidity [ 1 , 10 , 14 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 86%
“…STOPP section K included ‘benzodiazepines with history or risk of falls’ (22.1%), ‘neuroleptic drugs with history or risk of falls’ (10.2%), ‘hypnotic Z-drugs with history or risk of falling’ (2.8%) and ‘vasodilator drugs with orthostatic hypotension’ (0.1%). Detailed prevalences of all STOPP/START v2 can be found in our previous paper [ 16 ]. Three of the five most common STOPPFalls administered in our population belonged to the STOPPFall group opioids.…”
Section: Resultsmentioning
confidence: 99%
“…The technical translation of the Dutch STOPP criteria v2 has been described previously and was based on the consensus study of Huibers et al . [ 16 , 17 ]. In total, 68 STOPP criteria were included, coded by B.A.-D.V.…”
Section: Methodsmentioning
confidence: 99%
“…prospective vs. retrospective). For instance, a recent study found a lower prevalence of potential overuse (56%) and potential underuse (58%) after application of STOPP/START v2 algorithms on a database with medical information from older hospitalised patients [ 19 ]. Retrospective database studies are often limited by incomplete documentation of relevant medical information, directly affecting the prevalence of STOPP/START signals.…”
Section: Discussionmentioning
confidence: 99%
“…Missing data: renal function, 74 (9.0%); nursing home residents, 3 (0.4%); Barthel Index of ADL, 11 (1.3%); housebound, 2 (0.2%); number of falls during the previous year, 9 (1.1%); number of hospitalisations in the previous year, 3 (0.4%); length of stay during index hospitalisation, 2 (0.2%); admission type, 5 (0.6%) ADL activities of daily living, CKD-EPI chronic kidney disease epidemiology collaboration equation a ADL as measured by the Barthel Index. Values range from 0 to 100, with higher values indicating higher functional independence [18] Characteristics hospitalised patients [19]. Retrospective database studies are often limited by incomplete documentation of relevant medical information, directly affecting the prevalence of STOPP/ START signals.…”
Section: Frequency and Acceptancementioning
confidence: 99%